2005
DOI: 10.1093/jee/98.1.229
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Mealworm (Coleoptera: Tenebrionidae) Emergence After Mechanical Incorporation of Poultry Litter into Field Soils

Abstract: Lesser mealworm, Alphitobius diaperinus (Panzer), emergence from North Carolina field soils was evaluated in a controlled experiment simulating land application of turkey litter and again in field studies. Adult lesser mealworms were buried in central North Carolina Cecil red clay at depths of 0, 8, 15, 23, and 30 cm and the beetles emerging from the soil counted 1, 3, 7, 10, 13, 17, 21, 24, and 28 d after burial. Beetles emerged from all depths and differences among depths were not significant. Beetles surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
2
14
1
Order By: Relevance
“…However, in contrast with poultry farms, where A. diaperinus is, together with flies, the major insect pest (Strother & Steelman ; Calibeo‐Hayes et al . ; Retamales et al . ), data from faunistic studies in grain storage facilities classify A. diaperinus as a secondary insect pest of grains and related amylaceous commodities.…”
Section: Origins Distribution and Food Preferencesmentioning
confidence: 99%
“…However, in contrast with poultry farms, where A. diaperinus is, together with flies, the major insect pest (Strother & Steelman ; Calibeo‐Hayes et al . ; Retamales et al . ), data from faunistic studies in grain storage facilities classify A. diaperinus as a secondary insect pest of grains and related amylaceous commodities.…”
Section: Origins Distribution and Food Preferencesmentioning
confidence: 99%
“…Their mobility, indiscriminate feeding habits and their potential to then be preyed upon by poultry facilitate the dissemination of Salmonella . Current farm management practices perpetuate infestations and contribute to the dissemination of beetles and pathogens (Calibeo‐Hayes et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Producers are challenged to reduce pathogen load at the farm level; however, poultry management standards accept the reutilization of litter for successive flocks of broilers. The lesser mealworm can survive between flocks rotated onto the same litter, where they add to the bacterial exposure of the new flock or to the environment when the insect‐laden litter is removed for application onto nearby fields (Armitage 1986; Calibeo‐Hayes et al. 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Harein et al (1972) found that 27% of A. diaperinus samples collected from a turkey brooder house were positive for Salmonella. An infestation of A. diaperinus can be difficult to control, and these pests are often inadvertently dispersed to neighboring poultry houses and residences by the spreading of beetle-containing spent litter onto fields as fertilizers (Armitage 1986, Calibeo-Hayes et al 2005. Consequently, they are potential participants in the dissemination of pathogenic bacteria into the environment.…”
Section: Introductionmentioning
confidence: 99%